PENGARUH PERIKLANAN DAN KREDIBILITAS ENDORSER TERHADAP MINAT BELI E-COMMERCE SHOPEE DENGAN E-WOM SEBAGAI VARIABEL INTERVENING (SURVEY PADA PENGGUNA E-COMMERCE SHOPEE DI KOTA PONTIANAK) - Kurniaty, Dwi; Asih, Yekti Purwo; Indra, Indra (STIE 'INDONESIA' Pontianak, 2025)
This study aims to determine the effect of advertising, endorser credibility on purchase intention of e-commerce shopee where e-wom is an intervening variable. Based on previous research and associated with supporting theories put forward by experts using the SPSS program as a statistical data processing tool. This type of research is associative research. In this study, the researcher used a nonprobability sampling technique because the researcher did not know the total number of members of the population studied. The sample in this study was 100 samples.